FACTORS AFFECTING SEASONALITY IN THE STOCK MARKET: A SOCIAL NETWORK ANALYSIS APPROACH - Kajol, K.; Nath, Mausami; Singh, Ranjit; Singh, H. Ramananad; Das, Amit Kumar (International Journal of Accounting & Finance Review, 2020)
The study aims at identifying the factors influencing the seasonality effect in the stock market and further identifying the relationship between the influencing factors. The study aims at conducting a complete analysis of the influencing factors along with measuring their impact on seasonality using Social Network Analysis (SNA). The factors affecting the seasonality effect in the stock market were identified through the literature review. Experts’ opinions were sought for determining the relationship among the factors and finally, the importance of those factors was analyzed using Social Network Analysis (SNA). It was found that volatility is the most important factor affecting the other factors of seasonality and consequently seasonality effect finally. Besides, earning announcements, dividend, and January effects strongly influence the effect of seasonality in the stock market because of their higher in-degree and out-degree. To understand the mechanism of the stock market, the policymakers need to impart training to the investors through awareness campaign or by opening learning investors’ Club at different places. With this they can evaluate their standing in the stock market and the capability of bearing the risk which, in the long run, will be reflected in their investment behavior along with that the culture of equity investing will also be promoted among the investors.